Effect of Microcredit on Handloom Weavers of Grameen-Check Producers of Sirajganj District of Bangladesh: A Case Study in Six Selected Villages - Kamrun Nahar3 and Rehana Sultana4, N. M. Rahmatullah1*, Rokeya Begum2, (Journal of Experimental Sciences, 2010)
Handloom industry of Bangladesh is having wonderful past, debatable present and hazy future due to a lot of internal and external specter factors that are acting behind the sight. In this paper, we have identified those leading factors. The repayment behaviour of individuals suggests that the loans were properly used and that investment in handloom activities is profitable in the study area. It was found that the difference in previous financial conditions and financial conditions used after credit was statistically significant at the 0.001 level. It was also reported that taken credit was not sufficient at all for handloom weavers of the study areas. In our study area has 80.27 percent dependency ratio where as the national rural dependency ratio was 74.2%. Handloom weavers’ facing threats of destruction due to lack of Govt. patronage, shortage of funds abnormal price hike of yarn. <div style="border-right: medium none; padding-right: 0in; border-top: medium none; padding-left: 0in; padding-bottom: 1pt; border-left: medium none; padding-top: 0in; border-bottom: windowtext 1pt solid; mso-element: para-border-div; mso-border-bottom-alt: solid windowtext .5pt;"> Keywords: Microcredit, Grameen-check, Dependency ratio, Least significance difference and statistical inference 1Department of Agricultural Statistics, Sher-e-Bangla Agricultural University, Dhaka, Bangladesh; 2Agricultural Economics, Sher-e-Bangla Agricultural University, Dhaka, Bangladesh; 3Agricultural Botany, Sher-e-Bangla Agricultural University, Dhaka, Bangladesh; 4Individual Researcher, Dhaka, Bangladesh Please Cite This Article As: N. M. Rahmatullah, Rokeya Begum, Kamrun Nahar and Rehana Sultana. 2010. Effect of Microcredit on Handloom Weavers of Grameen-Check Producers of Sirajganj District of Bangladesh: A Case Study in Six Selected Villages. J. Exp. Sci. 1(4):21-26.